Reorientasi Tujuan Pendidikan Islam di Era Revolusi Industri 4.0: Kajian QS. Luqman/31: 13-17 - Sukarman Sukarman (Matan : Journal of Islam and Muslim Society, 2021)
Education ideally directs to the children’s natural disposition. However, the globalization and the industrial revolution as facts and realities have shifted the orientation of parents' thinking in interpreting educational goals. The objective of education, which should develop all human potential vertically and horizontally, changed direction to be oriented towards the material fulfillment. This research is a literature study using descriptive qualitative method. This research offered a solution in reorienting Islamic education through the interpretation of qv. Luqman/31: 13-17. The purpose of the research is to restore the orientation of education due to the impact of globalization and the 4.0 industrial revolution. The result showed that the verses is full of exemplary values ​​on how to be a good parent in accordance with the guidance of Islam. The verses offers the reorientation of Islamic education in the era of the industrial revolution which includes education on monotheism, personality, social ethics, and morals.